2013
DOI: 10.2478/s13382-013-0165-4
|View full text |Cite
|
Sign up to set email alerts
|

The role of occupational activities and work environment in occupational injury and interplay of personal factors in various age groups among Indian and French coalminers

Abstract: Objective: The role of occupational hazards in occupational injury may be mediated by individual factors across various age groups. This study assessed the role of occupational hazards as well as contribution of individual factors to injuries among Indian and French coalminers. Material and Methods: We conducted a case-control study on 245 injured workers and on 330 controls without any injuries from Indian coal mines using face-to-face interviews, and a retrospective study on 516 French coalminers using a sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
20
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 33 publications
6
20
1
1
Order By: Relevance
“…"Repeated injuries" was defined as two or more injuries. Similar questions have been used in adolescent and adult population studies (Bhattacherjee et al, 2013;Chau et al, 2008Chau et al, , 2011Hibell et al, 2004;Molcho et al, 2006).…”
Section: Single and Repeated School And Out-of-school Injuriesmentioning
confidence: 92%
See 1 more Smart Citation
“…"Repeated injuries" was defined as two or more injuries. Similar questions have been used in adolescent and adult population studies (Bhattacherjee et al, 2013;Chau et al, 2008Chau et al, , 2011Hibell et al, 2004;Molcho et al, 2006).…”
Section: Single and Repeated School And Out-of-school Injuriesmentioning
confidence: 92%
“…The results interpretation should be cautious as the 95% CIs of ORs were often overlapped. Various measures (socioeconomic factors, injuries, Table 4 Contribution of socioeconomic factors, school, behaviour and health-related difficulties to the associations between sleep difficulty and school and out-of-school single and repeated injuries (vs. none): odds ratio (OR), 95% confidence interval (CI) and contribution (% sleep difficulty, school performance, drug use, health status, psychological health, and involvement in violence) have been used in other studies (Bhattacherjee et al, 2013;Chau et al, 2008Chau et al, , 2011Hibell et al, 2004;Kandel and Davies, 1982;Leplège et al, 2000;Mayet et al, 2011;Molcho et al, 2006;Raphael et al, 2005;Skevington et al, 2004;Swanh et al, 2012). School performance and obesity were objective measures.…”
Section: Limitations and Strengthsmentioning
confidence: 99%
“…Health practice studies carried out on other groups have shown that the miners surveyed obtained a lower average point value score than e.g., the elderly (83.2-88.39), patients with cardiovascular diseases (78.31), patients with type 2 diabetes (92.92), or women who had undergone mastectomy (86.09) [12,15,16,20,21]. On a sten scale, the results obtained (3)(4) were also lower than those of the obese and overweight (5-6. sten) [20].…”
Section: Discussionmentioning
confidence: 99%
“…The research shows that most respondents occasionally treat people expressing concern about their health seriously (31%) and also seek to avoid strong emo- (12) 5 -"I limit the consumption of such products as animal fats or sugar" / "Ograniczam spożycie takich produktów jak tłuszcze zwierzęce, cukier" 37 (19) 88 (44) 47 (24) 19 (10) 9 (5) 9 -"I care about proper nutrition" / "Dbam o prawidłowe odżywianie" 15 (8) 38 (19) 80 (40) 48 (24) 19 (10) 13 -"I avoid foods containing preservatives" / "Unikam żywności z konserwantami" 35 (18) 77 (39) 54 (27) 26 (13) 8 (4) 17 -"I avoid salt and heavily salted food" / "Unikam soli i silnie solonej żywności" 23 (12) 76 (38) 59 (30) 31 (16) 11 (6) 21 -"I eat wholemeal bread" / "Jem pieczywo pełnoziarniste" 21 (911) 46 (23) 85 (43) 36 (18) 12 (6) Preventive actions / Zachowania profilaktyczne 2 -"I avoid common colds" / "Unikam przeziębień" 6 (3) 29 (15) 37 (19) 74 (37) 54 (27) 6 -"I have telephone numbers of emergency medical services at hand" / "Mam przygotowane numery telefonów służb pogotowia" 87 (44) 28 (14) 10 (5) 15 (8) 60 (30) 10 -"I abide by medical recommendations resulting from the examinations undergone" / "Przestrzegam zaleceń lekarskich wynikających z moich badań"…”
Section: Characteristics Of Individual Health Behavioursmentioning
confidence: 99%
See 1 more Smart Citation